A Narrative Review of Alveolar Bone Analysis and CBCT Classification related to Immediate Implant Placement in The Anterior Maxilla - Kamar Affendi, Nur Hafizah; Babiker, Jumanah; Mohd Yusof, Mohd Yusmiaidil Putera (Malaysian Journal of Medicine and Health Sciences, 2022)
Immediate implant placement into fresh extraction sockets has gained a lot of attention in implant dentistry. Besides proper risk assessment, the evaluation of tooth anatomy aids the clinicians to select the finest treatment protocol. Cone Beam Computed Tomography (CBCT) imaging was frequently used for alveolar bone analysis prior to tooth extraction in immediate implant placement. As an ideal position is required to prevent a buccally tilted implant or too palatal implant placement, various authors have proposed the treatment guidelines for immediate implant placement in the anterior maxilla. Although insightful, the previous classification was lacking anatomic variant and key anatomical features of alveolar bone and tooth angulation. Furthermore, there is no standardization method of measuring the specific degree of tooth angulation in CBCT scans that could possibly be used in clinical setting for appropriate treatment protocol. Thus, it is essential for the clinician to have adequate knowledge on the role of facial alveolar bone, palatal alveolar bone and tooth angulation related to immediate implant before selecting the appropriate treatment guidelines based on the classification reviewed. In this review, the previous quantitative measurements were categorized, and the previous classification was listed for the sake of familiarity by the dental practitioner with the major updates on implant placement strategy, patient selection and to reduce the rate of surgical complications